Tumor hijacks macrophages and microbiota through extracellular vesicles. Issue 1 (25th January 2022) - Jiang, Jipeng; Mei, Jie; Ma, Yongfu; Jiang, Shasha; Zhang, Jian; Yi, Shaoqiong; Feng, Changjiang; Liu, Yang; Liu, Ying
Abstract: The tumor microenvironment (TME) is a biological system with sophisticated constituents. In addition to tumor cells, tumor‐associated macrophages (TAMs) and microbiota are also dominant components. The phenotypic and functional changes of TAMs are widely considered to be related to most tumor progressions. The chronic colonization of pathogenic microbes and opportunistic pathogens accounts for the generation and development of tumors. As messengers of cell‐to‐cell communication, tumor‐derived extracellular vesicles (TDEVs) can transfer various malignant factors, regulating physiological and pathological changes in the recipients and affecting TAMs and microbes in the TME. Despite the new insights into tumorigenesis and progress brought by the above factors, the crosstalk among tumor cells, macrophages, and microbiota remain elusive, and few studies have focused on how TDEVs act as an intermediary. We reviewed how tumor cells recruit and domesticate macrophages and microbes through extracellular vehicles and how hijacked macrophages and microbiota interact with tumor‐promoting feedback, achieving a reciprocal coexistence under the TME and working together to facilitate tumor progression. It is significant to seek evidence to clarify those specific interactions and reveal therapeutic targets to curb tumor progression and improve prognosis. Abstract : Tumor‐derived extracellular vesicles can carry malignant factors from tumor cells and help hijack macrophages and microbiota in the tumor microenvironment (TME). In turn, the hijacked macrophages and microbiota can respond with tumor‐promoting feedback, achieving a reciprocal coexistence in the TME and working together to facilitate tumor progression.